A qualitative exploration of experiences and perceptions in recent parents screening positive for perinatal depression in Karachi, Pakistan - Atif, Maria; Saeed, Zeba; Halaki, Mark; Chow, Chin Moi; Raynes-Greenow, Camille (Journal of the Pakistan Medical Association, 2023)
The narrative review was planned to qualitatively analyse the experiences, factors and context of parents screening positive for perinatal depression in Karachi. Semi-structured in-depth interviews were conducted to explore the experiences and perceptions of participants during pregnancy, birth and 10-12 weeks after birth. Seven men and 20 women participated in the in-depth interviews. Factors in the perinatal period that affected new parents included sleep disturbances, emotional stressors linked to preference for a male child, a lack of social support, financial burdens of perinatal care, personal frustrations caused by an inability to comprehend the signs and symptoms of perinatal depression, denial to admit challenging issues concerning mental health and social disapproval with expressing mental health issues. There is an imminent need for appropriate initiatives to raise awareness about perinatal depression, and the provision of adequate perinatal mental health services for Pakistani women and men.